AB0755 The Predictive Role of High Sensitive C-Reactive Protein and High Density Lipoprotein in Development of Rotator Cuff Tear in Patients with Hand Osteoarthritis. (15th July 2016) - Kim, H.-O.; Suh, Y.S.; Cheon, Y.-H.; Park, K.S.; Kim, S.-H.; Lee, S.-I.
Abstract : Background: Rotator cuff tear (RCT) and hand osteroarthritis (HOA) are commonly accompanied because they share a similar pathogenesis. However, there was no previous study investigating the relationship between RCT and HOA. Objectives: To estimate the prevalence and associated factors of RCT in patients with HOA. Methods: In this study, we enrolled 1150 farmers who lived in Gyeongnam province in Korea from June 2013 to December 2015. Physical examinations were performed by rheumatologists and orthopedists. Plain radiography of hands and magnetic resonance imaging (MRI) of shoulders were performed in all participants. Serum levels of high sensitive C-reactive protein (hsCRP) and high density lipoprotein (HDL) were checked. RCT was diagnosed by clinical examination and MRI findings. Diagnosis of HOA was made by the 1990 American College of Rheumatology classification criteria. Severity of HOA was defined as Kellgren–Lawrence (KL) grade ≥3 on plain radiographs. Erosive HOA was defined as having eroded 'E' or remodelled 'R' phase of the Verbruggen. Results: The prevalence of RCT was higher in patients with HOA group (192/307, 62.5%) than those without HOA (410/827, 49.5%, p<0.010). Among 307 with HOA, patients with RCT were older (62.69±7.04 vs. 59.11 ±7.69, p<0.001) and showed higher hs-CRP (1.51±3.78 vs. 0.67±0.70, p=0.004) and lower HDL levels (55.66±15.46 vs. 60.48±12.45, p=0.003) compared to those without RCT. There were no significant differences in gender, smoking, comorbidities, work period, body mass index, number of affected joints, HOA severity, and prevalence of erosive HOA between both groups. Multiple logistic regression analysis showed significant associations of age (odds ratio [OR] 1.06; 95% confidence interval [CI] 1.02 - 1.10), serum levels of hsCRP (OR 1.37, CI 1.04 - 1.80), and HDL (OR 2.13, CI 1.14 - 3.98) with RCT in HOA patients. Conclusions: The prevalence of RCT is high and age and serum levels of hsCRP and HDL have predictive roles in the development of RCT in HOA patients. References: Jin X, Beguerie JR, Zhang W, Blizzard L, Otahal P, Jones G, Ding C. Extended report: Circulating C reactive protein in osteoarthritis: a systematic review and meta-analysis. Ann Rheum Dis 2015;74(4):703–10. Acknowledgement: This study was supported by a grant of the Center for Farmer's Safety and Health, Ministry of Agriculture, Food and Rural Affairs, Republic of Korea. Disclosure of Interest: None declared